Perancangan Federal Enterprise Architecture Framework Pengelolaan Surat Pada Dinas Perhubungan Kabupaten Sukabumi - Kareksi, Salsa Tini; Saepudin, Sudin (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2021)
The Sukabumi Regency Transportation Office has several fields, one of which is the Head of the General and Civil Service Sub-section which has the function of collecting and processing data. This function, of course, is mostly carried out by the letter archiving department because this section is the most important part or can be called the heart of the Sukabumi Regency Transportation Service. Where the section regulates the management of incoming letters, outgoing letters, and mail reports. Mail management activities still use agenda books, disposition cards and Microsoft Office so that mail management activities are still not optimal. From the letter management activities at the Sukabumi Regency Transportation Office, several problems were found, namely there was a loss of incoming mail data in 2019 reaching 50% while errors in letter data collection occurred in outgoing mail data reaching 10-40% so that it could affect the reporting of the number of letters. The Transportation Agency of Sukabumi Regency must realize Enterprise Architecture to be able to regulate and supervise the management of letters. With this in mind, the researcher will make a "Design of the Federal Enterprise Architecture Framework on Mail Management at the Sukabumi Regency Transportation Service". This will be a solution to these problems, this research will produce a framework (blueprint) in the form of business architecture, data architecture, application architecture, and technology architecture.